PROFIL KEPERCAYAAN DIRI SISWA KELAS VIII MTS YPPS SUKAMISKIN - Indira Aristianti; Nelly Fitriani; Azni Nurul Fauzia (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Self-confidence is one of the essential aspects of students' personal development and academic success. This study aims to describe the level of self-confidence among eighth-grade students at MTs YPPS Sukamiskin. The research used a descriptive quantitative method, involving 28 students selected through purposive sampling. The research instrument was a self-confidence questionnaire based on Lauster’s theory (1992), and the data were analyzed using a score categorization technique. The results showed that 29% of students were in the low category, 57% in the moderate category, and 14% in the high category. These findings indicate that most students require reinforcement of their self-confidence in order to participate more actively and believe in their potential. Therefore, structured and continuous guidance and counseling services need to be designed to support students in developing more stable and consistent self-confidence, so that they are better prepared to face academic and everyday life challenges with greater confidence and independence.